Targeting plasmodium α-tubulin-1 to block malaria transmission to mosquitoes - Zhang, Genwei; Niu, Guodong; Hooker–Romera, Diana; Shabani, Sadeq; Ramelow, Julian; Wang, Xiaohong; Butler, Noah S.; James, Anthony A.; Li, Jun (Frontiers in Cellular and Infection Microbiology, 2023)
Plasmodium ookinetes use the invasive apparatus to invade mosquito midguts, and tubulins are the major structural proteins of this apical complex. We examined the role of tubulins in malaria transmission to mosquitoes. Our results demonstrate that the rabbit polyclonal antibodies (pAb) against human α-tubulin significantly reduced the number of P. falciparum oocysts in An. gambiae midguts, while rabbit pAb against human β-tubulin did not. Further studies showed that pAb, specifically against P. falciparum α-tubulin-1, also significantly limited P. falciparum transmission to mosquitoes. We also generated mouse monoclonal antibodies (mAb) using recombinant P. falciparum α-tubulin-1. Out of 16 mAb, two mAb, A3 and A16, blocked P. falciparum transmission with EC50 of 12 μg/ml and 2.8 μg/ml. The epitopes of A3 and A16 were determined to be a conformational and linear sequence of EAREDLAALEKDYEE, respectively. To understand the mechanism of the antibody-blocking activity, we studied the accessibility of live ookinete α-tubulin-1 to antibodies and its interaction with mosquito midgut proteins. Immunofluorescent assays showed that pAb could bind to the apical complex of live ookinetes. Moreover, both ELISA and pull-down assays demonstrated that insect cell-expressed mosquito midgut protein, fibrinogen-related protein 1 (FREP1), interacts with P. falciparum α-tubulin-1. Since ookinete invasion has direction, we conclude that the interaction between Anopheles FREP1 protein and Plasmodium -tubulin-1 anchors and directs the ookinete invasive apparatus towards the midgut PM and promotes the efficient parasite infection in the mosquito.